Characterization of tribological behavior of chromium and zinc coatings electrodeposited on a steel substrate - Rhaiem, S.; Nasri, F.; Kharrat, M.; Dammak, M. (Фізико-хімічна механіка матеріалів, 2014)
Three coatings of decorative chromium, hard chromium and zinc, electrolytically deposited on the C45 steel substrate, are considered in this study. Experimental characterization of the tribological response of the substrate and different coatings against spherical 100Cr6 counterbody is developed with a linear reciprocating tribometer. The results show that the three coatings have similar values for the stabilized coefficient of friction which remains substantially higher than the value of the friction coefficient for the substrate. The decorative chromium coating has the lowest wear resistance. A better wear resistance is obtained with the zinc coating. The first place in terms of wear resistance is occupied by the hard chromium coating and the uncoated substrate which have similar resistance. Досліджено трибологічну поведінку трьох видів електролітичних покривів: декоративного хрому, твердого хрому та цинку, сформованих на підкладці зі сталі C45. Використано трибометр за умов зворотно-поступального руху контртіла. Виявлено, що для всіх покривів значення стабілізованого коефіцієнта тертя однакові, однак, істотно вищі, ніж для підкладки. Покрив з декоративного хрому має найнижчий опір зношуванню, а вищу зносотривкість – цинковий. Найвища зносотривкість властива покриву з твердого хрому та підкладці без покриву. Исследовано трибологическое поведение трех видов электролитических покрывов: декоративного хрома, твердого хрома и цинка, сформированных на подкладке из стали C45. Использован трибометр при условиях возвратно-поступательного движения контртела. Обнаружено, что для всех покрывов значения стабилизированного коэффициента трения одинаковые, однако, существенно выше, чем для подкладки. Покрыв из декоративного хрома обладает наиболее низким сопротивлением изнашиванию, а цинковый наиболее износостойкий. Наивысшая износостойкость свойственна покрыву из твердого хрома и подкладке без покрыва.